Students’ perceptions and preferences of educational assessments during the infection prevention and control course - Moolman, Antoinette (My University, 2018)
Introduction: The competency of the students attending the infection prevention and control course (IPC) at a selected university in Gauteng is of concern because they frequently fail to achieve a pass mark in their final examination. Infection prevention and control is a clinical field and needs a high level of application of what was studied in the IPC course. As the problem of hospital-acquired infections rises, this low competency rate impacts on the number of trained and competent infection prevention and control practitioners and thus on the effective management of the hospital infection rate. The summative marks of the students in a specific study group indicate a problem which may relate to either the teaching, the selection of the students or the assessment methods used. Some effort has already been made to improve teaching. Little could be done regarding selection since due to the shortage of infection prevention and control practitioners, all applicants are accepted onto the course. A concern is that the current use of multiple choice questions as a sole evaluation method is not the best option or method of evaluation for this group of students. The following question needs to be answered: What methods of assessment do the IPC students prefer and what are their perceptions of multiple choice question examinations? Objective: The objectives of the study were to explore the preferences of IPC students of assessment methods used in the IPC course and to explore the perception of the IPC students of the computer based multiple choice questions method of assessment used in the IPC course. Methodology: This study made use of an exploratory and qualitative design that included semi-structured interviews which took place in small groups in an attempt to gather in-depth information which was analysed as described by Clarke and Braun (2013). The population in this study consisted of all students registered on the IPC course who took part in examinations from 2011-2016. Semi-structured interviews which took place in six small groups were conducted until saturation was achieved. Trustworthiness was based on the model of Lincoln and Guba. Results: Three themes and eight subthemes derived from the semi-structured interviews which took place in small groups. Participants discussed broadly the evaluation process, the use of computer based multiple choice questions and alternative methods of assessment regarding their preferences and perception during the IPC course. Conclusion: The purpose of the study was to gain more insight into students’ actual preferences of assessment methods and their perceptions of computer-based multiple choice questions examinations. In order to fulfill the purpose of this study two objectives were set and achieved. The findings showed that timing of testing, the content of examinations and preparation for examination as part of the evaluation process were issues the students needed to deal with to pass. Unfamiliarity with the format, negative marking as an assessment method and English as a language of instruction course increased anxiety of the student participating in the course. Rationale for alternative forms of evaluation and the 5 recommendations for alternative methods of assessment need to be considered in further changes of the curriculum in future. Keywords: Infection prevention and control, multiple choice questions, evaluation approaches, evaluation methods, infection prevention and control courses, semi-structured interviews and e-learning in infection prevention and control.
A research report submitted to the Faculty of Health Science, University of the Witwatersrand, Johannesburg in fulfilment of the requirements for the degree of Master of Science in Nursing, Johannesburg 2018
Keywords: Infection control; Communicable Disease Control